Review paper of gateway selection schemes for MANET of NEMO (MANEMO) - Mahmood, Zainab S.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Anwar, Farhat; Hameed, Shihab A. (IOP Publishing, 2013)
The fast growth of Internet applications brings with it new challenges for researchers to provide new solutions that guarantee better Internet access for mobile hosts and networks. The globally reachable, Home-Agent based, infrastructure Network Mobility (NEMO) and the local, multi-hop, and infrastructure-less Mobile Ad hoc Network (MANET) developed by Internet Engineering Task Force (IETF) support different topologies of the mobile networks. A new architecture was proposed by combining both topologies to obtain Mobile Ad Hoc NEMO (MANEMO). However, the integration of NEMO and MANET introduces many challenges such as network loops, sub-optimal route, redundant tunnel problem, absence of communication without Home Agent reachability, and exit router selection when multiple Exit Routers to the Internet exist. This paper aims to review the different proposed models that could be used to implement the gateway selection mechanism and it highlights the strengths as well as the limitations of these approaches.